STRATEGY OF LEARNING THE QURAN USING THE IQRO METHOD FOR THE ELDERLY COMMUNITY IN BREBES DISTRICT - Alipah, Alipah (Sekolah Tinggi Agama Islam Al Hidayah, 2026)
Background: Adult or elderly learning with children's learning has relative differences. Children's teaching is done through the identification and imitation stages, while adult teaching uses the self-direction stage to deal with a problem. Research Objective: This article aims to examine the strategy of learning the Qur'an using the Iqro method for the elderly at MTQ Assa'adah Brebes. Research Method: This study uses a qualitative approach with a phenomenological method. The data collection technique uses documentation, observation and interviews. The data analysis techniques are data reduction, data display, and conclusion. Research Results: The Qur’anic learning strategies at MTQ Assa’adah, Brebes Regency, for elderly learners are implemented through approaches tailored to the needs of older adults. These strategies include tadrij (gradual learning), which begins with the introduction of hijaiyah letters and progresses slowly toward mastery of tajwid and tartil in accordance with the cognitive abilities of elderly learners. In addition, the taqrir (repetition) strategy is employed to strengthen memory and comprehension through systematic repetition of learning materials. The sorogan strategy emphasizes individualized learning, in which learners recite the Qur’an directly in front of the educator, allowing for personal interaction and precise correction. The implementation of these three strategies has been shown to have a positive impact on improving elderly learners’ ability to read the Qur’an correctly and with proper tartil. Conclusion: The main findings of this study indicate that the integrated application of tadrij, taqrir, and sorogan strategies is effective in enhancing elderly learners’ ability to read the Qur’an accurately and fluently. Gradual learning supports step-by-step comprehension, repetition strengthens memory retention, and sorogan facilitates individualized instruction through direct interaction between educators and learners, making Qur’anic learning for the elderly more optimal and meaningful.